IOT BASED CROP FIELD MONITORING SYSTEM - Sai Kumar Y, Nohith Raj K, Bhavani U, Sai Kiran T, Bhanujyothi H C (International Journal of Advanced Science and Technology, 2020)
Smart farming is a management concept focused on providing the agricultural industry with the infrastructure to leverage advanced technology – including big data, the cloud and the internet of things (IoT) – for tracking, monitoring, automating and analyzing operations. Also known as precision agriculture, smart farming is software-managed and sensor-monitored. Smart farming is growing in importance due to the combination of the expanding global population, the increasing demand for higher crop yield, the need to use natural resources efficiently, the rising use and sophistication of information and communication technology and the increasing need for climate-smart agriculture. This paper incorporates advancement of a framework which may screen temperature, humidity, wet and even the development of animals which can pulverize the harvests in horticultural field through sensors misuse Arduino board and just if there should be an occurrence of any inconsistency send a SMS warning in like manner as a notice on the machine produced for a comparable to the rancher's cell phone.